Contesting globalization : space and place in the world economy - Drainville, André C., 1963- (Routledge/RIPE series in global political economy. RIPE series in global political economy., 2004)
An innovative and original addition to the literature on globalization which examines the challenges faced by those wishing to develop progressive visions of transparent global governance and civil society.